The impact of uncertain nuclear masses near closed shells on the r-process abundance pattern. (5th February 2015) - Mumpower, M; Surman, R; Fang, D L; Beard, M; Aprahamian, A
Abstract: Calculations of rapid neutron capture nucleosynthesis involve thousands of pieces of nuclear data for which no experimental information is available. Of the nuclear data sets needed for r -process simulations—masses, -decay rates, -delayed neutron emission probabilities, neutron capture rates, fission probabilities and daughter product distributions, neutrino interaction rates—masses are arguably the most important, because they are a key ingredient in the calculations of all other theoretical quantities. Here, we investigate how uncertainties in nuclear masses translate into uncertainties in the final abundance pattern produced in r -process simulations. We examine the influence of individual mass variations on three types of r -process simulations—a hot wind, cold wind, and neutron star merger r process—with markedly different r -process paths and resulting final abundance patterns. We find the uncertainties in the abundance patterns due to the mass variations exceed the differences due to the astrophysics. This situation can be improved, however, by even modest reductions in mass uncertainties.